On a Convergence of the Modified Fourier-Pade Approximations - Tigran Bakaryan (National Academy of Sciences of Armenia)
We consider convergence acceleration of the modified Fourier expansions by trigonometric-rational corrections which lead to the modified Fourier-Pade approximations. Exact constants of the asymptotic errors are derived for smooth functions and the comparison with the corresponding errors of the modified Fourier expansions is performed.
Keywords: Approximations and expansions